Volcanism in The Pre-Semilir Formation at Giriloyo Region; Allegedly as Source of Kebo-Butak Formation in the Western Southern Mountains - Sri Mulyaningsih; Muchlis Muchlis; Nur W.A.A.T. Heriyadi; Desi Kiswiranti (Journal of Geoscience, Engineering, Environment, and Technology, 2019)
Kebo-Butak Formation was known to be the oldest volcanic rocks limited in regional terms in the lower Baturagung Hills, Gedangsari area, Gunungkidul Regency. The main constituents of the Kebo-Butak Formation consist of intersection of volcanic-clastic rocks and calcareous sediments, locally also found basalt lava with pillow structures; which distinguished it from other volcanic rock formations in the Southern Mountains. This study aims to determine the relationship of volcanic rocks exposed in Giriloyo with the Kebo-Butak Formation in the Baturagung Hills; the chronostratigraphy and the history of volcanic activities that produced the volcanic rocks of Giriloyo. This research was approached by volcanic geological mapping using surface mapping suported by gravity anayses. From the bottom to the top of the frontier areas result volcaniclastic rocks consisting of black tuffs with several fragments of volcanic bombs with basalt composition intersecting with thin basaltic lava inserted by calcareous claystone having an age of N5-7 (Early Miocene); pyroxene-rich basalt volcanic sequence consists of thick layers of tuff with creamy-brown color intersecting with lava and breccia inserted by calcareous sandstone aged N7-8; dikes, lava and agglomerates with basaltic composition and lava and agglomerates with andesitic composition. Stratigraphically, the volcanic rocks exposed at Giriloyo correlated with the volcanic rocks exposed at Karangtalun (Wukirsari) were under the Semilir Formation, bordered with normal fault N210oE/77o, the hanging wall composed by light grey tuff of Semilir Formation. Gravity analyses found high anomalies below the Semilir Formation exposed at Karangtalun-Munthuk (east of study area) continued to below the Giriloyo area. The high anomalies were identified as the igneous/ignimbrite volcanic sequence. Descriptively and stratigraphically, the Giriloyo volcanic sequence are a part of Kebo-Butak Formation. The petrogenesis of the volcanic rocks will be discussed in further research to interpret magmatological properties, the evolving paleo-volcano, and the absolute age of the rocks.